PELAYANAN DALAM BAHASA INGGRIS SEBAGAI UPAYA MENINGKATKAN KUALITAS SERVICE EXCELLENT DI DESA BANTAR AGUNG - Inpresta Natalia; Aam Amaliah; Dariyanto Dariyanto; Diniawati Aliyah; Devi Nopianti (JURNAL ABDIMAS PLJ, 2026)
Bantar Agung Tourism Village in Majalengka Regency holds vast potential for international tourism, yet the limited English proficiency of local operators remains a primary barrier to achieving service excellence. Although the village boasts highly attractive natural tourism potentials, it still faces significant challenges in reaching international tourists due to foreign language communication constraints, particularly in English. This community service initiative aims to enhance human resource capacity through practical English for Tourism communication training, focusing on introducing tourist attractions, explaining travel routes, answering visitor inquiries, and conveying local culture and history. The program's implementation methodology includes interactive lectures, intensive training using the role-play method, and interactive Q&A and discussion sessions. The results indicate a significant increase in the operators' confidence and speaking skills when welcoming international tourists. Standardized greetings, safety instruction delivery, and complaint handling now strictly align with service excellence principles. The implication of this program is the establishment of a more professional, welcoming, and globally competitive service standard to support the sustainability of the creative economy in Bantar Agung Village.